The Syntax of Assertion in the Poetry of Claudio Rodriguez - Margaret H. Persin (Studies in 20th & 21st Century Literature, 1986)
Through his original and unsettling manner of syntactical assertion, Claudio Rodriguez, the contemporary Spanish poet, subverts the conventional usage of language. But, in turn, he captures the transcendental, magical experience of language and all existence in the process of the text. That experience is based on intuition, irrationality and sensorial associations, rather than on logical connections. The reader is thus confronted with texts whose contradictory interpretive paths of signification continually subvert one another. Rodriguez wishes to communicate that it is not the end result but rather the process of the text that is the ultimate meaning. The reader's task is to participate in that process and experience firsthand the intricacies of Rodriguez's intuitive approach to reality. The characteristics of an intuitive approach to reality, irrationality, and sensorial associations establish a historical and literary connection between Rodriguez's work and that of the Surrealists.
Keywords: Claudio Rodriguez; Spanish literature; contemporary Spanish poets; contemporary poetry; language; transcendental; magical; sign; signification; reality; irrationality; sensory; sensorial associations; Surrealists; surrealism